Abuse‐deterrent extended‐release oxycodone and risk of opioid‐related harm. (18th January 2021) - Paljarvi, Tapio; Strang, John; Quinn, Patrick D.; Luciano, Sierra; Fazel, Seena
Abstract: Aim: To establish and quantify the association between abuse‐deterrent formulation (ADF) oxycodone and 1‐year risk of opioid‐related harm. Design: Propensity score‐matched cohort study of electronic medical records for years 2014–18, with patients followed up for 1 year after their index health‐care visit. Setting: More than 70 million patients from 56 US health‐care organizations. Participants: Patients aged 18–64 years at index health‐care visit with any indication for an oral opioid analgesic, with no past 12‐month history of oral oxycodone use or substance use disorder, and who were alive at the end of the 1‐year follow‐up (new episode of prescription oral ADF oxycodone [OxyContin], n  = 45 045; new episode of non‐ADF oxycodone opioid preparation, n  = 1 377 359). Measurements: International Classification of Diseases diagnoses of any opioid‐related disorder or non‐fatal opioid poisoning within 1 year of the index health‐care visit. Pooled odds ratios (OR) with 95% confidence intervals (95% CI). Findings: After propensity score matching, 89 802 patients with a mean age of 44 [standard deviation (SD) = 11] years (62% women, 68% white) were included. During 1‐year follow‐up, 1445 diagnoses of opioid use disorder or opioid poisoning occurred in the ADF oxycodone cohort (34.8/1000 person‐years) and 765 occurred in the non‐ADF oxycodone cohort (18.2/1000 person‐years). The odds of opioid‐related adverse outcomes were increased in the ADF oxycodone cohort compared with the non‐ADF oxycodone opioid cohort, including for opioid use disorders (OR = 2.02; 95% CI = 1.83, 2.23) and opioid poisoning (OR = 1.64 95% CI = 1.35, 1.99). Conclusions: Patients with a new prescription of abuse‐deterrent formulation oxycodone may be at increased risk of opioid‐related harm.